ANALISIS ESTETIKA ANIMASI 2 DIMENSI CERITA RAKYAT ASAL-USUL BATURRADEN PADA YOUTUBE DONGENG TANAH JAWA - Amirah, Yumna (ASKARA: Jurnal Seni dan Desain, 2023)
Baturraden is one of the areas in the province of Central Java. The name Baturraden was created from folklore. In fact, not many local people, especially children, know the origins of the creation of Baturraden. Therefore we need media that can attract the attention of children namely is through 2-dimensional animation which can be accessed easily via YouTube. This study uses a qualitative descriptive analysis approach using the science of aesthetics. The theory of aesthetics uses a theoretical approach according to Djelantik which describes aesthetics into three basic elements, namely form, weight, and appearance. A 2-dimensional animation of the folk story "Origin of Baturraden", using a cartoon-style illustration. The type of typography used belongs to the decorative style with a touch of serif fonts. The most common colors used are pink, yellow, orange, brown, purple, indigo, blue, green, gray, black, and white. While the arrangement in the animation refers to shots, scenes, and sequences. The atmosphere that was built is around the duchy area with traditional nuances and beautiful nature typical of ancient times. The message that I want to convey is that if you want to get something you want, you have to fight and try hard. Besides that, there is also a message to act sincerely in order to bring success in the future.